2006
DOI: 10.1673/2006_6_30.1
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity and differentiation among populations of the Indian eri silkworm, Samia cynthia ricini, revealed by ISSR markers

Abstract: Samia cynthia ricini (Lepidoptera:Saturniidae), the Indian eri silkworm, contributes significantly to the production of commercial silk and is widely distributed in the Brahmaputra river valley in North-Eastern India. Due to over exploitation coupled with rapid deforestation, most of the natural populations of S. cynthia ricini are dwindling rapidly and its preservation has become an important goal. Assessment of the genetic structure of each population is a prerequisite for a sustainable conservation program.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
12
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 33 publications
2
12
0
1
Order By: Relevance
“…However, the genetic diversity of S. cynthia ricini at the strain level (PPB = 20.83%; h = 0.0858; I = 0.1244) was well within the range calculated by Vijayan et al (2006). UPGMA analysis of Indian populations showed that the individuals grouped according to their population affi nity, and none changed its population cluster, which was different from that found in Chinese populations (Fig 1).…”
Section: Genetic Diversitymentioning
confidence: 56%
See 4 more Smart Citations
“…However, the genetic diversity of S. cynthia ricini at the strain level (PPB = 20.83%; h = 0.0858; I = 0.1244) was well within the range calculated by Vijayan et al (2006). UPGMA analysis of Indian populations showed that the individuals grouped according to their population affi nity, and none changed its population cluster, which was different from that found in Chinese populations (Fig 1).…”
Section: Genetic Diversitymentioning
confidence: 56%
“…This is a pattern frequently observed in wild plants (Zhang et al 2007, Tahan et al 2009 and wild insects (Moya et al 2001, Gallusser et al 2004. However, only 16% of genetic variation occurred within strains and 84% among strains of B. mori in China, as observed in Indian populations of S. cynthia ricini (Vijayan et al 2006). This pattern is also found in many domesticated animals (Huang et al 1996, Hao et al 2000 and cultivated plants .…”
Section: Genetic Distancementioning
confidence: 76%
See 3 more Smart Citations